Rehabilitation outcome of progressive multifocal leukoencephalopathy in HIV-positive patients: a report of two cases. Issue 18 (28th August 2017) - Moreh, Elior; Israel, Sarah; Korem, Maya; Meiner, Zeev
Abstract: Purpose: To describe the rehabilitation treatment and outcome of progressive multifocal leukoencephalopathy (PML) in the context of Human Immunodeficiency Virus (HIV). Method: The medical history of two HIV-positive patients with PML was reviewed; information on their neurological impairments, rehabilitation treatment and outcome was gathered. Results: The patients, a 47-year-old married man and a 34-year-old single man, both suffered from dense right hemiplegia and motor aphasia. Their rehabilitation course was delayed and prolonged: they were suitable for intensive multidisciplinary rehabilitation only 8 months or more after the initial presentation. Their treatment in outpatient rehabilitation daycare three times a week, that lasted 7 months on average, resulted in slow and steady functional improvement. At the end of the rehabilitation treatment, both patients were living at home, able to express themselves, and able to walk independently with an assistive device. They remained with moderate disability (modified Rankin scale of 3). Conclusion: PML patients require prolonged multidisciplinary rehabilitation treatment; however, considerable progress can be achieved. Implications for Rehabilitation: Progressive multifocal leukoencephalopathy (PML) is a disabling disease occurring in particular in the context of Human Immunodeficiency Virus (HIV). Presently a growing number of HIV-positive PML patients eventually survive the disease and remain with severe neurological impairments. PML patients require prolonged multidisciplinary rehabilitation treatment, and considerable progress can be achieved.